Population habits in household solid waste management:: a case study in Juazeiro do Norte ”“ CE - Feitosa, Anny Kariny; Barden, Júlia Elisabete; Hasan, Camila; Konrad, Odorico (Sustainability in Debate, 2016)
The aim of this study is to analyze populational habits in handling and disposal of domestic solid waste in the city of Juazeiro do Norte, Ceará State, through interviews applied to 53 households in six neighborhoods classified in the socioeconomic strata A, B1, B2, C1, C2 and D. Results point out that 62.26% of the households discarded organic waste through the conventional collection system of the municipality; 81.13% discarded plastic waste through the conventional collection system, 15.09% donated waste to street collectors; 24.53% discarded cooking oil through the conventional collection system, 30.19% poured cooking oil into the sink drain and 20.76% devoted cooking oil waste to the production of soap; 84.91% discarded used batteries through the conventional collection system, 1.89% burned or buried them and 5.66% left the batteries in establishments certified for reverse logistics. It is necessary to invest resources in educational campaigns to inform on proper disposal procedures of solid waste in municipalities, thus contributing to the sustainable development of the region.